2017
DOI: 10.1111/jir.12389
|View full text |Cite
|
Sign up to set email alerts
|

Autism awareness in children and young people: surveys of two populations

Abstract: Children and young people have good levels of awareness and knowledge about autism and reported positive attitudes towards peers with autism and are willing to help those who are bullied. A higher than expected number of children and young people self-reported being on the autism spectrum. These findings bode well for peer-mediated support strategies for inclusive education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…Increased awareness of autism among peers has been proposed as a strategy to prevent pupils with ASD being isolated and bullied. Dillenburger et al (2017) examined 3353 11-year-old to 16-year-old pupils and found that awareness of autism was higher among teenagers (80%) than younger children (50%). Many children knew someone with autism (50%) and generally indicated positive and supportive attitudes.…”
Section: Mainstream School and Special Solutions For Pupils With Asdmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased awareness of autism among peers has been proposed as a strategy to prevent pupils with ASD being isolated and bullied. Dillenburger et al (2017) examined 3353 11-year-old to 16-year-old pupils and found that awareness of autism was higher among teenagers (80%) than younger children (50%). Many children knew someone with autism (50%) and generally indicated positive and supportive attitudes.…”
Section: Mainstream School and Special Solutions For Pupils With Asdmentioning
confidence: 99%
“…Many children knew someone with autism (50%) and generally indicated positive and supportive attitudes. Peers believed bullying was a problem but wanted to help those who were bullied (Dillenburger et al 2017). Munkhaugen et al (2017) reported that refusal to attend school among pupils with ASD has only been studied to a limited extent, but is considered a serious problem.…”
Section: Mainstream School and Special Solutions For Pupils With Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…Awareness of ASC is also reasonably high among children and teenagers in the UK [11]. Children generally report positive attitudes to peers with ASC, and many identify bullying as an issue commonly faced.…”
Section: View Of the General Publicmentioning
confidence: 99%
“…Participation in the training was associated with decreased stigma and increased knowledge in both countries. Dillenburger, Jordan, McKerr, Lloyd, and Schubotz (2017) identified the level of autism awareness among children and youth. Results indicated that autism awareness was higher for teenagers (80%) than for the younger children (50%).…”
mentioning
confidence: 99%